The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/membranes12010051
|View full text |Cite
|
Sign up to set email alerts
|

Osmium Recovery as Membrane Nanomaterials through 10–Undecenoic Acid Reduction Method

Abstract: The recovery of osmium from residual osmium tetroxide (OsO4) is a necessity imposed by its high toxicity, but also by the technical-economic value of metallic osmium. An elegant and extremely useful method is the recovery of osmium as a membrane catalytic material, in the form of nanoparticles obtained on a polymeric support. The subject of the present study is the realization of a composite membrane in which the polymeric matrix is the polypropylene hollow fiber, and the active component consists of the osmiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 64 publications
3
24
1
Order By: Relevance
“…45 µg/mL). This observation is in agreement with previous data, which showed that the loss of 10-undecenoic acid in a membrane can be reduced by using electrolyte additives (NaCl or NaNO3) [28][29][30].…”
Section: The Influence Of the Ionic Strength Of The Silver Ions And 1...supporting
confidence: 93%
See 2 more Smart Citations
“…45 µg/mL). This observation is in agreement with previous data, which showed that the loss of 10-undecenoic acid in a membrane can be reduced by using electrolyte additives (NaCl or NaNO3) [28][29][30].…”
Section: The Influence Of the Ionic Strength Of The Silver Ions And 1...supporting
confidence: 93%
“…These observations are in agreement with the previous results [28][29][30] and are correlated with the size and distribution of macro-porous pores of the membrane surface on which the dispersion of silver-containing oxide nanoparticles is impregnated in the first days of contact (Figure 8). At a longer operating time, a balance is achieved between the concentration of ions in the impregnated membrane and that of the ions in the receiving aqueous system.…”
Section: Influence Of Membrane Support Morphology and Silver Content ...supporting
confidence: 93%
See 1 more Smart Citation
“…Among the metallic nanoparticles, those based on osmium have been relatively little studied [ 14 , 15 , 16 ], with one of the reasons being toxicity [ 17 ]. In reality, osmium is an inert metal with remarkable potential mechanical, thermal, electrical and catalytic properties, and its toxicity is related to osmium tetroxide that appears on the metal surface from contact with air [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, osmium nanoparticles have been deposited either on flat membranes with the aim of initiating reaction processes [ 14 ], or on hollow fiber membranes with the aim of increasing the contact surface between the phases of the membrane system [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%